Impact of natural disasters on school attendance: A comparative study from colonial Jamaica - Joel Huesler (European Historical Economics Society (EHES), 2024)
This paper investigates the impact of hurricanes on school attendance in Jamaica from 1892 to 1942, a period marked by significant natural disasters, including four category two hurricanes. By integrating monthly school attendance data from the fourteen Jamaican parishes with assessments of potential storm destruction, the paper quantifies the effect of hurricanes on school attendance. The average effect of a category two hurricane was a 9.1% decrease in school attendance in the month of the hurricane, followed by decreases of 8.6% and 7.2% in the following two months. Consequently, nearly 400 children miss school for one month, with over 310 children missing school for three months. Mediation analysis further indicates a decline in school performance by up to 3.23%, indirectly caused by decreased school attendance. This paper highlights the lasting impact of hurricanes on educational outcomes, especially in countries with agrarian economies and underdeveloped education systems.
Keywords: I25; N36; N96; Q54; 330; Education; Environmental Economic History; Natural Disasters